2002
DOI: 10.1523/jneurosci.22-04-01238.2002
|View full text |Cite
|
Sign up to set email alerts
|

Mechanosensitive Ion Channels in Cultured Sensory Neurons of Neonatal Rats

Abstract: Mechanosensitive (MS) ion channels are present in a variety of cells. However, very little is known about the ion channels that account for mechanical sensitivity in sensory neurons. We identified the two most frequently encountered but distinct types of MS channels in 1390 of 2962 membrane patches tested in cultured dorsal root ganglion neurons. The two MS channels exhibited different thresholds, thus named as low-threshold (LT) and high-threshold (HT) MS channels, and sensitivity to pressure. The two channel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
121
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(126 citation statements)
references
References 47 publications
5
121
0
Order By: Relevance
“…7, 2018; evoked current did not affect the channel activation threshold (-37.1 + 3.2 mm Hg, n=47) or the percentage of active patches (82%, 47 of 57 patches). This elevated activation threshold is similar to that observed in cultured primary nociceptors (Cho et al, 2002), also known as high-threshold mechanonociceptors, highlighting another similarity between TACAN and the endogenous channel found in nociceptors. In stably transfected CHO cells, we determined the single-channel conductance of the MSC induced by TACAN proteins.…”
Section: Tacan Expression Increases Mechanically-evoked Currents In Hsupporting
confidence: 78%
See 1 more Smart Citation
“…7, 2018; evoked current did not affect the channel activation threshold (-37.1 + 3.2 mm Hg, n=47) or the percentage of active patches (82%, 47 of 57 patches). This elevated activation threshold is similar to that observed in cultured primary nociceptors (Cho et al, 2002), also known as high-threshold mechanonociceptors, highlighting another similarity between TACAN and the endogenous channel found in nociceptors. In stably transfected CHO cells, we determined the single-channel conductance of the MSC induced by TACAN proteins.…”
Section: Tacan Expression Increases Mechanically-evoked Currents In Hsupporting
confidence: 78%
“…A different MSC, termed Piezo2, plays a crucial role in sensing touch but not mechanical pain (Ranade et al, 2014b). Moreover, Piezo2 displays rapid adapting kinetics and a higher conductance than the one identified in nociceptors (Cho et al, 2006;Cho et al, 2002;Coste et al, 2010). In contrast, TACAN displays slow-adapting kinetics, lower conductance, and when its expression is reduced, leaves responses to touch intact but impairs those to mechanical pain.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that filamentous actin (Factin) can either participate in the gating of mechanosensitive channels (Su et al, 2000;Cho et al, 2002;Piao et al, 2003) or protect against their activation by mechanical stimuli by providing physical support for the plasma membrane (Hamill and McBride, 1997;Ko and McCulloch, 2000;Morris, 2001). To determine whether F-actin is required for mechanical regulation of SIC channels, we quantified transducer sensitivity in MNCs pretreated (30 -60 min) with Cyt-D (200 -250 M), a drug that depolymerizes F-actin (Cooper, 1987), or JSK (2.5 M), a drug that promotes actin polymerization (Bubb et al, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…The mean reversal potential of the osmotically evoked current was Ϫ27.6 Ϯ 4.5 mV, consistent with the involvement of nonselective cation channels under our experimental conditions (see Discussion). Additionally, increases in membrane conductance induced by hyperosmolality could be reversed by bath application of 300 M Gd 3ϩ (⌬G ϭ 0.51 Ϯ 0.15 nS before and ⌬G ϭ Ϫ0.16 Ϯ 0.06 nS after Gd 3ϩ ; n ϭ 8; p ϭ 0.003; data not shown), a blocker of nonselective cation channels (Hase et al, 1995;Cho et al, 2002).…”
Section: Osmosensory Transduction Involves Hypertonicity-activated Camentioning
confidence: 91%